Implementasi Keselamatan, Kesehatan Kerja dan Lingkungan pada Proyek Pembangunan Convention Hall Kalianda (International Forum of Researchers and Lecturers, 2025)
Occupational Safety and Health is a field related to the health, safety, and welfare of people working in an institution or at a project site. PT Rindang Tigasatu Pratama is a company engaged in the construction services sector that has been established since 1980 in Kotabumi, North Lampung Regency. The Kalianda Convention Hall construction project is one of the projects carried out by PT Rindang Tigasatu Pratama as a contractor. The results of the observation showed that only 43% of the 44 workers always wore helmets. The use of safety vests was even lower, at 27%. As many as 68% of workers always wore boots. For gloves, only 30% of workers consistently used them. On the other hand, all workers showed a high awareness of the importance of ensuring safe working conditions to ensure safety and smooth work. These findings highlight the need for further efforts to increase awareness and comfort in the use of personal protective equipment among construction workers.